APPLICATION OF UV SPECTROPHOTOMETER AND HPLC ON ANALYSIS OF CAFFEINE CONTENT IN ARABICA AND ROBUSTA COFFEES - Prasetyo, Dedy; Sitorus, Saibun; Gunawan, Rahmat (JURNAL ATOMIK, 2020)
Analysis of caffeine content in Arabica coffee and Robusta coffee using Ultra Violet (UV) spectrophotometers and High Performance Liquid Chromatography (HPLC) was carried out. Coffee samples were soxhleted with 96% ethanol with the rotation variation used, namely 4, 6, 8, 10 and 12. The extract was dissolved in 96% ethanol and tested with a UV spectrophotometer. The results obtained caffeine content in arabica coffee for 4, 6, 8, 10 and 12 rotations are 1.347 mg/L, 1.631 mg/L, 1.953 mg/L, 2.868 mg/L and 3.764 mg/L respectively. While the caffeine content obtained by Robusta coffee for 4, 6, 8, 10 and 12 turns are 1.820 mg/L, 2.258 mg/L, 2.741 mg/L, 3.814 mg/L and 4.781 mg/L, respectively. Caffeine content in Arabica and Robusta coffee were analyzed by HPLC. The results obtained in Arabica coffee are retention time of 5.079 minutes, area of 1265348 and height of 56539 and in Robusta coffee the retention time is 5,083 minutes, the area is 1249273 and the height is 55700.